2007
DOI: 10.1038/sj.bjc.6603953
|View full text |Cite
|
Sign up to set email alerts
|

First-into-man phase I and pharmacokinetic study of XR5944.14, a novel agent with a unique mechanism of action

Abstract: The bis-phenazine XR5944.14 is a novel cytotoxic agent which intercalates into DNA and inhibits transcription. The objectives of this study were to determine the dose-limiting toxicity (DLT), the maximum tolerated dose (MTD) and to describe the pharmacokinetics (PKs) of XR5944.14 when given at doses ranging from 3.6 to 36 mg m À2 every 3 weeks to patients with advanced tumours. Twentyseven patients were treated with a total of 77 cycles. Dose-limiting toxicities occurred at doses X24 mg m À2 . Oral mucositis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In 2007, a dose-escalation phase I trial described the first administration of XR5944 (21) to a human as a 30-min infusion every 3-4 weeks [70]; however, the lack of correlation between toxicity and PK values made it difficult to recommend a dose for further study in phase II trials ( Table 1). More work is needed to explain the intra-and interindividual variation in drug handling.…”
Section: Phenazine Derivatives Xr11576 (20) and Xr5944 (21)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2007, a dose-escalation phase I trial described the first administration of XR5944 (21) to a human as a 30-min infusion every 3-4 weeks [70]; however, the lack of correlation between toxicity and PK values made it difficult to recommend a dose for further study in phase II trials ( Table 1). More work is needed to explain the intra-and interindividual variation in drug handling.…”
Section: Phenazine Derivatives Xr11576 (20) and Xr5944 (21)mentioning
confidence: 99%
“…In view of their interesting activity, both compounds have entered preclinical trials [70,71]. Assayed in vivo, XR11576 (20) proved to be extremely active against human colon and small cell lung cancer xenografts and showed activity against multidrug resistant cells over-expressing Pglycoprotein, or multidrug resistance-associated proteins (MRP) as well as cells with down-regulation of topoisomerase II levels [72].…”
Section: Phenazine Derivatives Xr11576 (20) and Xr5944 (21)mentioning
confidence: 99%
“…The toxicity of SN26700 and SN26871 however, is diminished some 35 to 2200 times in the RMS panel, with their IC 50 s clustering around m or greatly exceeding it ( Figure 2). The exceptional response is found with SN26356 which was used in clinical trial as MLN944/XR5944 (Verborg et al, 2007). Its potent activity in previous studies is maintained in the RD, RH3 and RH4 cell lines, with an average IC 50 of about 40 nM.…”
Section: Cytotoxicity Of Novel and Established Transcription Inhibitomentioning
confidence: 91%
“…It has then been demonstrated that XR5944 displays its potent cytotoxic effects through inhibition of transcription of all RNA polymerases (Byers et al 2005). XR5944 (MLN944) was co-developed by Millenium Pharmaceuticals and Xenova Ltd. and has entered phase I clinical trials in 2003 as a therapeutic agent for solid tumours (Byers et al 2005;Verborg et al 2007). However, the lack of correlation between toxicity and PK values made difficult to recommend of dose for further study in Phase II trials (Verbog et al 2007) and this compound does not seem to have entered Phase II clinical trials in oncology, at least to the best of our knowledge.…”
Section: Dimeric Phenazinesmentioning
confidence: 99%